An assessment of the knowledge processing environment in an organisation : a case study - Vlok, Daniël (Rhodes University, Faculty of Commerce, Investec Business School, 2004)
Knowledge Management is associated with organisational initiatives in response to the demands of a knowledge-based economy in which the potential value of knowledge as a source for competitive advantage is recognised. However, the lack of a common understanding about knowledge itself, its characteristics and how it is constructed has led to diverse approaches about how to "manage" it. This study presents a critical overview of traditional and contemporary KM approaches. The main focus of this study was to discover and apply a suitable methodology for assessing an organisation's knowledge processing environment. This includes an analysis of the current practices and behaviours of people within the organisation relating to the creation of new knowledge and integrating such knowledge into day-to-day work. It also includes inferring from the above practices those policies and programmes that affect knowledge outcomes. This research makes extensive use of the Knowledge Life Cycle (KLC) framework and the Policy Synchronisation Method (PSM) developed by advocates of the New Knowledge Management movement. A case study approach was followed using a range of data collection methods, which included personal interviews, a social network survey and focus group discussions. The selected case is the small IT department at the East London campus of Rhodes University. Evidence from the case suggests that the knowledge processing environment within the IT department is unhealthy. The current knowledge processing practices and behaviours are undesirable and not geared towards the creation of new knowledge and the integration of such knowledge within the business processes of the IT department. There is little evidence of individual and organisational learning occurring and the problem solving process itself is severely hampered by dysfunctional knowledge practices. The study concludes that the above state of affairs is a reflection of the quality and appropriateness of policies and programmes in the extended organisation. Equally, the local definition of rules, procedures and the execution thereof at a business unit level is mostly lacking. The study illustrates that a systematic assessment of the knowledge processing environment provides the organisation with a sound baseline from where knowledge-based interventions can be launched.
Keywords: Rhodes University (East London) -- Information Technology Department; Knowledge management; Organizational behavior; Organizational learning; Information storage and retrieval systems